PERANCANGAN VIDEO INSPIRATIF FASHION BATIK DALAM UPAYA MENGANGKAT NILAI BATIK SEBAGAI TREND NASIONAL - Hanif, Gabiella; Rahmadyanto, Sultan Arief; Nugroho, Didit Prasetyo (Ma Chung Press, Universitas Ma Chung, 2024)
Designing an inspirational video about Batik is an activity to process a video following current trends with the aim of inspiring Indonesian teenagers to wear batik as their identity clothing. Batik is one of the artistic treasures that has been preserved from generation to generation by the people of Indonesia. Batik art has received recognition in the world as a cultural heritage of the archipelago, through its illustrated cloth by making distinctive, traditional, pictorial patterns. Its use in everyday life is a way of respecting the nation's traditions and cultural heritage. We. The number of new fashion modes in people's clothing styles as time goes by changes the function and meaning that is valued by society. Therefore, the author intends to create an inspiring fashion video trend to inspire young people in Indonesia by updating their mindset regarding modern Batik and as a medium for inspiring them to wear batik clothing as an identity of the Indonesian nation that is best preserved.